2022
DOI: 10.1515/jcim-2020-0305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of complementary spiritual therapy on stress, anxiety, burnout syndrome and hematological parameters of professionals in a public hospital: a randomized controlled trial

Abstract: Objectives This randomized controlled trial evaluated the stress, anxiety, and burnout of professionals exposed to complementary spiritist therapy (CST), which consists in therapeutic resources as prayer, Spiritist passe, fluidic water and spiritual education or control. Methods Seventy-six professionals were randomized to CST or control: to maintain the routine for 5 weeks. The ISSL scale, anxiety and depression Beck’s indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…The Complementary Spiritist Therapy that comprised therapeutic resources of spiritist guidance, as praying, spiritist "passe", fluidified water and spiritual education or spiritual control was conducted in a randomized controlled trial with professionals of a Brazilian public hospital and has demonstrated a medium efficacy on the reduction of stress in the intervention group in comparison to control group. The outcomes showed that a higher number of interventions of spiritist therapy raised the sample effect (Carneiro et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…The Complementary Spiritist Therapy that comprised therapeutic resources of spiritist guidance, as praying, spiritist "passe", fluidified water and spiritual education or spiritual control was conducted in a randomized controlled trial with professionals of a Brazilian public hospital and has demonstrated a medium efficacy on the reduction of stress in the intervention group in comparison to control group. The outcomes showed that a higher number of interventions of spiritist therapy raised the sample effect (Carneiro et al, 2022).…”
Section: Discussionmentioning
confidence: 98%